Algorithm Aided Design Framework for BIM: Daylight In Early Phases of Design - Koçak, Can; Alaçam, Sema (Estoa, 2023)
This study proposes an algorithm-aided design (AAD) framework for using daylight in the early phases of architectural design. Within the scope of the proposed AAD, a performance-based design approach has been adopted that can suggest design solutons by optmising with the Genetc Algorithm (GA) that evaluates the results obtained from daylight calculaton. The AAD framework was developed using the visual programming applicaton (Dynamo), which interoperates with BIM Sofware Autodesk Revit. A case study is simulated to show how the algorithm is used to generate, evaluate and evolve a massing study, demonstratng the potental use and implementaton of the framework. The investgatons focus on the development of the use of daylight in architecture using the advantages of computatonal design tools.